2009
DOI: 10.4103/0378-6323.55392
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of references cited in articles published in indian journal of dermatology, venereology and leprology: A pilot study

Abstract: RESULTS of this pilot study suggest that improving accuracy of the references is important. Solutions to this problem are suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…From other sources we included four additional studies. In total, we included 28 studies in our main analysis ( De Lacey, Record & Wade, 1985 ; Lowry, 1985 ; Eichorn & Yankauer, 1987 ; Neihouse & Priske, 1989 ; Evans, Nadjari & Burchell, 1990 ; Hobma & Overbeke, 1992 ; Puttermann, 1992 ; Goldberg et al, 1993 ; George & Robbins, 1994 ; Hansen & McIntire, 1994 ; Warren et al, 1997 ; Schulmeister, 1998 ; Lawson & Fosker, 1999 ; Lee & Lee, 1999 ; Fenton et al, 2000 ; Pieters, Ceysens & De Heyn, 2001 ; Gosling, Cameron & Gibbons, 2004 ; Lukić et al, 2004 ; Buchan, Norris & Kuper, 2005 ; Gupta et al, 2005 ; Reddy et al, 2008 ; Al-Benna et al, 2009 ; Singh & Chaudhary, 2009 ; Awrey et al, 2010 ; Davids et al, 2010 ; Mertens & Baethge, 2011 ; Buijze et al, 2012 ; Luo et al, 2013 ) and three in an additional analysis (see Fig. 1 for PRISMA flowchart).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From other sources we included four additional studies. In total, we included 28 studies in our main analysis ( De Lacey, Record & Wade, 1985 ; Lowry, 1985 ; Eichorn & Yankauer, 1987 ; Neihouse & Priske, 1989 ; Evans, Nadjari & Burchell, 1990 ; Hobma & Overbeke, 1992 ; Puttermann, 1992 ; Goldberg et al, 1993 ; George & Robbins, 1994 ; Hansen & McIntire, 1994 ; Warren et al, 1997 ; Schulmeister, 1998 ; Lawson & Fosker, 1999 ; Lee & Lee, 1999 ; Fenton et al, 2000 ; Pieters, Ceysens & De Heyn, 2001 ; Gosling, Cameron & Gibbons, 2004 ; Lukić et al, 2004 ; Buchan, Norris & Kuper, 2005 ; Gupta et al, 2005 ; Reddy et al, 2008 ; Al-Benna et al, 2009 ; Singh & Chaudhary, 2009 ; Awrey et al, 2010 ; Davids et al, 2010 ; Mertens & Baethge, 2011 ; Buijze et al, 2012 ; Luo et al, 2013 ) and three in an additional analysis (see Fig. 1 for PRISMA flowchart).…”
Section: Resultsmentioning
confidence: 99%
“…In evaluating manuscripts: Editors (e.g., Lee & Lee, 1999 ; Singh & Chaudhary, 2009 ) and Reviewers (e.g., Schulmeister, 1998 ; Lukić et al, 2004 ) should check selected references.…”
Section: Discussionmentioning
confidence: 99%
“…[25] Stated that "If a reference contains citation errors, it becomes difficult for the interested reader to obtain full text of the paper. On the other hand, if a quotation error is present, the base on which the entire work intends to build on becoming questionably quoted.…”
Section: Resultsmentioning
confidence: 99%
“…Studies using the traditional journal based approach have reported that between 10% and 50% of papers contain citation inaccuracies (1,13). Only a few studies have reported a rate of inaccurate citations below 10% (14,15).…”
Section: Discussionmentioning
confidence: 99%